Modeling and Simulation of ABS through Different Types of Controllers Using Simulink - Wafi, Mohammed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The ABS system is an abbreviation of the Anti-lock Brake System. Anti-lock brake system is the most important development in automotive technology for vehicle and traffic safety improvements. This system is used widely to ensure safe braking. Accident investigators have noticed that some of accidents happen and become a matter of concern, due to various human errors. But the most of traffic accidents occur because of faults in any mechanical system in vehicle, and/or bad condition of the roads. Bosch company was the leader in this field. It was the first company that invented and produced this system in 1978, and the brakes were designed in Anti-lock to implement the technique of braking technology automatically without the intervention of the vehicle driver. Through an electro-hydraulic control system, where an electronic control unit works to control the activation or non-activation of the hydraulic control system via the controlling of screw valves based on the signal sent from a number of sensors and switches. As the wheel speed sensors work to determine the speed and slowdown of the wheels. This signal is sent to the electronic control unit, if the wheels are slowing sharply, i.e. about to close, the control unit issues instructions to the hydraulic group. Then hydraulic group will reduce the brake pressure on these tires. And prevent the lock from occurring. When the driver continues to press the brake pedal, the pressure rises again. And this process is repeated several times until the vehicle stops completely. In this thesis, the subsystems and dynamics of ABS will be explained. Then a model of ABS will be created in MATLAB/SIMULINK software. While simulation of ABS model achieved by applying different control strategies as: Bang-bang which acts as on/off, PID and PD controller, with a vehicle speed of 100km/hr moving in straight line. Simulation will analyze the behavior of vehicle under application of ABS and without implementation of ABS mode, through different road types. Keywords: Anti-lock braking system (ABS), locking, slipping, PID controller, PD controller, simulation, vehicle dynamics.

ÖZ: ABS sistemi, Kilitlenmeyi Önleyici Fren Sisteminin bir kısaltmasıdır ve kilitlenmeyi önleyici fren sistemi, araç ve trafik güvenliği iyileştirmeleri için otomotiv teknolojisindeki en önemli gelişmedir ve güvenli frenleme sağlar, Kaza müfettişleri, çeşitli insan hatalarından dolayı bazı kazaların meydana geldiğini fark etmiş ve endişe konusu haline gelmiştir, ancak trafik kazalarının çoğu araçtaki herhangi bir mekanik sistemdeki arızalar ve / veya yolların kötü durumundan kaynaklanmaktadır, Bosch firması bu alanda lider olmuş ve bu sistemi 1978 yılında icat eden ve üreten ilk firma olmuştur, ve frenler, araç sürücüsünün müdahalesi olmadan fren teknolojisi tekniğini otomatik olarak uygulamak için kilitlenmeyecek şekilde tasarlanmıştır. Bir elektronik kontrol ünitesi, bir dizi sensör ve anahtardan gönderilen sinyale bağlı olarak vidalı valflerin kontrolü yoluyla hidrolik kontrol sisteminin etkinleşmesini veya etkinleşmemesini kontrol etmek için bir elektro-hidrolik kontrol sistemi aracılığıyla sağlar. Tekerlek hız sensörleri tekerleklerin hızını ve yavaşlamasını belirlemeye çalıştığı için bu sinyal elektronik kontrol ünitesine gönderilir, tekerlekler keskin bir şekilde yavaşlıyorsa, yani kilitlenmek üzereyse, kontrol ünitesi, kilidin oluşmasını önlemek için bu lastikler üzerindeki fren basıncını azaltmak için hidrolik gruba talimatlar verir. Sürücü fren pedalına basmaya devam ettiğinde basınç tekrar yükselir ve bu işlem araç tamamen durana kadar birçok kez tekrarlanır. Bu tezde ABS sisteminin alt sistemleri ve dinamikleri anlatılacak, ardından MATLAB/SIMULINK yazılımında bir ABS sistemi modeli oluşturulacak, ABS modelinin simülasyonu ise açma/kapama işlevi gören Bang-bang, PID ve PI denetleyici gibi farklı kontrol stratejileri araç 100 km/sa hızında doğrusal olarak hareket ederken uygulanarak elde edilmiştir. Simülasyon, ABS uygulaması altında ve ABS modu uygulanmadan, farklı yol türleri aracılığıyla aracın davranışını analiz edecektir. Anahtar Kelimeler: Kilitlenmeyi önleyici fren sistemi (ABS), kilitleme, kayma, PID denetleyici, PD denetleyici, simülasyon, araç dinamiği.
Master of Science in Mechanical Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2016. Supervisor: Assoc. Prof. Dr. Hasan Hacışevki.
Keywords: Mechanical Engineering; Automobiles--Automatic Control--ABS (Anti-lock Braking System); Anti-lock braking system (ABS); locking; slipping; PID controller; PD controller; simulation; vehicle dynamics